A study on the temperature dependence of the quasi-two-dimensional electron concentration and mobility in AlxGa1-xAs/GaAs selectively doped heterostructures - Simserides, C.D.; Triberis, G.P. (Journal of Physics: Condensed Matter, 1995)
We present a quantitative analysis of the temperature dependence of the quasi-two-dimensional electron concentration in AlxGa1-xAs/GaAs heterostructures taking into account the fact that in the bulk Si-doped AlxGa1-xAs two types of donor coexist, i.e. deep and shallow, which independently, and by different mechanisms, provide electrons to the bulk AlxGa1-xAs different conduction band minima and to the quasi-two-dimensional electron gas (Q2DEG). We calculate the electronic states, the ionized-donor concentrations, the Q2DEG and the bulk-electron concentrations and the corresponding mobilities as a function of temperature. Our numerical results are in very good agreement with the experimental data.